Analysis Prediction of Financial Distress in Islamic Commercial Banks in Southeast Asia Using the Springate S-Score Method - Anisa Septiawan; Hilda Monoarfa; Aneu Cakhyaneu (Journal of Islamic Economic and Business Research, 2024)
Financial distress is a condition of financial difficulties before entering the bankruptcy stage, so bankruptcy itself is the impact of financial distress, and the company can no longer be saved. The chaotic economy caused by the COVID-19 pandemic had a negative impact on various sectors, especially Islamic banking institutions, which experienced a decline in financial performance and even experienced financial distress. The purpose of this study is to analyze the prediction of financial distress in Islamic Commercial Banks in Southeast Asia using the Springate S-Score method, as well as to see and determine differences in the level of financial distress in each Islamic Commercial Bank that is used as the research sample. The research method used in this research is quantitative, and the research design used is descriptive and comparative. This study used a purposive sampling technique with a sample of 4 Islamic Commercial Banks in Southeast Asia with a 5 year research period. The data analysis applied descriptive analysis techniques, the Springate S-Score method, and the ANOVA Test. The results of this study indicate that each Islamic commercial bank used as a sample is categorized as distressed based on Springate calculations for the 2017-2021 period, and there are differences in financial distress conditions at each bank.